Penegakan Hukum Terhadap Pelanggaran atas Ketentuan Perizinan Toko Swalayan di Wilayah Provinsi Bali - Suantra, I Nengah; Nurmawati, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
The Self-service shop developing into the countryside, however there are those who do not have licenses and violated licensing regulation. Therefore, violations of law were identified and analyzed by supermarkets, and law enforcement by SATPOL PP against these violations. Research uses normative legal research methods; the approach is the legislative approach, concepts, and philosophy. Data sources consist of primary, secondary, and tertiary legal materials and the results of interviews with informants. The arrangement of the Self-service shop’s licenses is performed with Local Regulation, Regent Regulation, Regulation of Mayor, and/or the Mayor's Decision, the Mayor's Instructions and Regent's Circular Letter. Klungkung District does not have a regulation for supermarket yet. The legality of the Self-service shop is in the form of IUTS/IUTM, IUPP, DUTS, and DUPP. Tabanan and Klungkung District use SIUP and TDP. The law infringement of the Self-service shop is: violation of working time, distance of location, not having an IUTS, not applying a new license application in moving the location, and selling liquor. The law enforcement conducted by providing verbal warning, written warning, founding, applying for the licenses, and/or business suspension. The legality of the Self-service shop must use IUTS, and Klungkung District immediately formed regulation for the Self-service shop are. The un-licensed Self-service shop are monitored and evaluated continuously and identified the licenses that have been issued. Law enforcement for unlicensed and illegal Self-service shops that are permitted to be done explicitly and consistently so as not to cause injustice in society. Toko swalayan menjamur hingga ke pedesaan, namun ada yang tidak berizin, dan melanggar ketentuan perizinan. Penelitian dilakukan untuk mengidentifikasi dan menganalisa pelanggaran hukum oleh toko swalayan, dan penegakan hukum oleh SATPOL PP terhadap pelanggaran tersebut. Penelitian menggunakan metode penelitian hukum normatif; pendekatannya yaitu pendekatan perundang-undangan, konsep, dan filsafat. Sumber data terdiri atas bahan hukum primer, sekunder, dan tersier serta hasil wawancara dengan informan. Pengaturan izin toko swalayan dilakukan dengan Perda, Perbup, Perwali, dan/atau Keputusan Walikota, Instruksi Walikota dan Surat Edaran Bupati. Kabupaten Klungkung belum memiliki Perda toko swalayan. Legalitas toko swalayan berbentuk IUTS/IUTM, IUPP, DUTS, dan DUPP. Kabupaten Tabanan dan Klungkung menggunakan SIUP dan TDP. Pelanggaran hukum toko swalayan yaitu: pelanggaran jam kerja, jarak lokasi, tidak memiliki IUTS, tidak mengajukan permohonan izin baru dalam memindahkan lokasi, dan menjual minuman beralkohol. Penegakan hukum dilakukan dengan memberikan peringatan lisan, tertulis, pembinaan, mengajukan izin, dan/atau pembekuan usaha. Legalitas toko swalayan supaya menggunakan IUTS, dan Kabupaten Klungkung segera membentuk Perda toko swalayan. Toko swalayan yang tidak berizin supaya dimonitoring dan dievaluasi secara berkelanjutan serta diidentifikasi izin yang sudah terbit. Penegakan hukum terhadap toko swlayan yang tidak berizin dan yang melanggar izin supaya dilakukan secara tegas dan konsisten agar tidak menimbulkan ketidakadilan dalam masyarakat.